Caries sicca: tuberculosis of glenohumeral joint - Goel, Varun; Sharma, Pankaj Kumar; Jain, Jalaz; Yadav, Umesh; Devgan, Ashish; Bhardwaj, Neha (International Journal of Research in Orthopaedics, 2019)
Tuberculosis is quite common in India. Shoulder tuberculosis although rare among the skeletal tuberculosis needs to be kept in mind for diagnosis and proper treatment of cases of Carries Sicca. Twenty year old female presented with non traumatic pain in right shoulder with severe restriction of shoulder Range of Movements (ROM), not responding to treatment. On detailed examination turned out to be a case of Caries Sicca. Thorough debridement along with sufficient immobilization and Anti Tubercular Treatment (ATT) gives excellent results. High suspicion is needed to diagnose the cases of Carries Sicca. Early diagnosis and proper treatment gives wonderful results. Only ATT with or without immobilization and debridement are sufficient enough in majority of cases.